Overview of Nutritional Status of Patients with Chronic Kidney Disease Who Undergoing Hemodialisis - Ismunandar, Ismunandar; Collein, Irsanty; Khaira, Nuswatul (Poltekkes Kemenkes Palu, 2024)
Patients undergoing hemodialysis for a period of more than 3 years tend to experience malnutrition due to inadequate food intake, diseases of the digestive tract, eating restrictions, drugs that cause impaired nutrient absorption, inadequate dialysis, and comorbidities. This study aimed to determine the relationship between nutritional status and the quality of life of chronic kidney disease patients undergoing hemodialysis in Palu. This study used a quasy experiment design to determine the the 2-mean difference test.. The sample formula determined the number of samples to test the hypothesis on the average of two populations with 100 respondents. This study was carried out in 2 hemodialysis units in Palu. The samples involved in this study were selected by simple random sampling. The KDQOL SF-36 is used to measure quality of life, whereas the malnutrition inflammation score is employed in the questionnaire used to assess nutritional status. The results of this study show that most respondents are in the age range of > 55 years, with 60 people (60%); are female, with 48 people (48%). 48% have a poor quality of life, and 52% have a good quality of life. The p-value for MIS is 0.001, so it can be concluded that at 5% alpha, there is a significant difference between the malnutrition inflammation score before and after education, while there is no significant difference for quality of life and kt/v values. There is an influence of health education on patient nutrition, there is no influence of health education using the KADOic application on quality of life and kt/v.